A REVIEW OF QUR’ANIC VERSES ON MAHR IN ISLAMIC FAMILY LAW - Nugroho, Nasywa Nabilah; Sukiati, Sukiati; Fatimah, Fatimah (Program Pascasarjana UIN Sumatera Utara, 2026)
This study examines the concept of mahr in Islamic marriage by analyzing Qur’anic verses that affirm mahr as a fundamental right of women and a binding obligation upon men. Rather than viewing mahr solely as a normative legal requirement, this research highlights its function as an instrument of protection, welfare, and honor for women. Using a literature-based approach, the study explores key Qur’anic passages such as QS al-Nisā’ 4, QS al-Baqarah 237, and QS al-Nisā’ 24, supplemented with classical tafsīr and contemporary fiqh scholarship. The findings indicate that the Qur’an emphasizes that mahr must be given sincerely and through mutual agreement, reflecting core principles of justice, consent, and marital commitment. Beyond its material form, mahr carries symbolic and spiritual value, serving as a tangible expression of goodwill and respect. It also functions as a financial safeguard, particularly in cases of divorce. This research concludes that the Qur’anic framework of mahr remains highly relevant in addressing modern social, economic, and cultural challenges surrounding marriage practices, and provides a normative foundation for implementing mahr that is equitable, proportional, and conducive to the well-being of contemporary Muslim families.